Indian psychiatrists in the Australian workforce – From brain drain to brain exchange. (July 2022) - Pai, Nagesh; Gupta, Rahul; Lakra, Vinay; Vella, Shae-Leigh; Kalra, Harish; Yadav, Tarun; Chaturvedi, Shailja; Gill, Neeraj S
Worldwide doctors have been migrating from low- and middle-income countries to high-income countries for decades. This contributes to dearth of doctors, especially psychiatrists, in low- and middle-income countries – often referred to as 'brain drain'. Australia has a fair share of psychiatrists of Indian origin in its workforce. This article endeavours to re-formulate the migration phenomenon as 'brain exchange' through the experiential insight of the authors along with published literature and discusses the contribution of substantial number of psychiatrists of Indian origin to the Australian society. Furthermore, the article highlights the potential for the Royal Australian and New Zealand College of Psychiatrists to be a leader in this area by facilitating globally responsible practice by giving back to countries from which psychiatrists originate. The key observations and recommendations are transferrable to other similar countries and equally to other medical specialities.